PENGARUH GPM (GERAKAN PESANTREN MENYENANGKAN) TERHADAP KEJADIAN BULLYING PADA SANTRI DENGAN PENDEKATAN TEORI PERUBAHAN KURT LEWIN - Dela, Jamaludin Arya; Ghofar, Abdul; Yani, Athi’ Linda (Jurnal EDUNursing, 2021)
AbstractBullying is one of a nature of hurting or distrubing behaviours toward victim, the victim can be a person or group. The Prevalence of bullying mostly occurs among adolescents, especially adolecents who are live in boarding schools. Many efforts have been made to prevent bullying, but this problem is still appearance until nowdays. The methodology research on this study was used literature review obtained PubMed, Science Direct, DOAJ, and Google Scolar. This study also obtined 10 literature. There results of this study found that there was an influence of GPM (Gerakan Pesantren Menyenangkan) to bullying incidence among santri by using Kurt Lewin's Change Theory. GPM (Gerakan Pesantren Menyenangkan) is a program to emotions  expression of santri, the happy, sad and angry expression can expresses or mentions in emotional zone which available in their room, so this will make their friends know what are their felling and this also make sense between the santri then the environment became more conducive and of prevent bullying behavior among santri. The implementation of the GPM program by using Kurt Lewin's  Change Theory  has 3 stages,  The first stage Unfreezing, Santri committed to implementing the program, as well get an understanding of bullying. The second stage Moving,  Santri run the GPM program so that the environmental conditions are orderly and conducive. The third stage Refreezing, santri agreed and carried out and obeyed the rewards and regulations understanding of bullying. Keywords : Bullying, GPM Programe, Kurt Lewin's Change Theory.